ENHANCING STUDENTS – PRE SERVICE TEACHER INTERACTION USING FIRST LANGUAGE (L1) IN ENGLISH FOR YOUNG LEARNERS (EYL) CLASSES - Setyaningrum, Rina Wahyu; Sabgini, Kharisma Naidi Warnanda; Setiawan, Slamet (LET: Linguistics, Literature and English Teaching Journal, 2020)
For any different objectives of teaching EYL at primary schools in Indonesia, qualified EYL teachers are urgently needed. Pre-service teaching program is expected to provide experience of using proper English language in classroom setting. This case study aimed at describing the first language (L1) instruction used by the pre-service teachers of English for Young Learners (EYL) at the Universitas Muhammadiyah Malang (UMM). The findings depicted that L1 was used as a language of instruction to explain the materials and to clarify the instruction given in L2. It is recommended for the pre-service teachers of EYL to use L2 with demonstration, L2 Context Clues, and L1 translation. Ultimately, the use of L1 in L2 teaching is mandatory to communicate the topic and enhance the students - pre-service teacher interactions. As for meeting the purpose of interaction, the use of L1 should involve actional, conversational, and non-verbal competences. In the long run, the impact of L1 in L2 learning in earlier levels can be recognized from good interpersonal communication in English.